Heidegger on ontotheology : technology and the politics of education - Thomson, Iain D. (Iain Donald), 1968- (Cambridge University Press, 2005)
Restoring Heidegger's understanding of metaphysics as 'ontotheology' to its rightful place at the center of his later thought, this book demonstrates the depth and significance of his controversial critique of technology, his appalling misadventure with Nazism, and his important philosophical suggestions for the future of higher education.